RARELY DETECTED COMPLICATION DURING CATHETERIZATION OF INTERNAL JUGULAR VEIN - DAMAGE TO THE VAGUS NERVE - M. V. Bykov; V. V. Lazarev; K. S. Madorskii; V. G. Bagaev; L. V. Bykova (SINAPS LLC, 2017)
In the course of intensive therapy for central venous catheterization is a high risk of mechanical complications. The probability of damage to the nervus vagus in the catheterization internal jugular vein is very high, but the lack of vigilance of medical personnel and damage to the knowledge of the clinical picture does not allow prevent and register this type of complication. The purpose of research - the use of ultrasound in the diagnosis of the location of the n.vagus to prevent damage during puncture and catheterization IJV. In the process of intensive care at various emergencies in 100 children aged from 2 weeks to 17 years, conducted IJV ultrasound to identify anatomic relationships of the internal jugular vein, carotid artery and n.vagus . At 30 children ultrasound preceded IJV catheterization (static method) and then selecting the most safe vascular access to the IJV. Dynamic method of ultrasound guidance during IJV catheterization was performed аt 26 саses. We made a retrospective analysis of a series of stationary cards of patients in the intensive care ward with suspected damage to the vagus nerve as a result of catheterization (attempts) IJV. Results - when the preliminary ultrasoundneurovascular bundle all the children had rendered the vagus nerve. Selection of the optimal, secure access to the IJV on the basis of static methods and ultrasound assisted of catheterization allowed to successfully catheterize IJV and avoided mechanical complications, including damage of the nervus vagus. Retrospective analysis of stationary cards of patients allow to think about the presence of such complications are not recorded according to medical records.